Faktor-Faktor yang Mempengaruhi Perilaku Orang Tua dalam Memberikan Pendidikan Seksual pada Anak Difabel di SLBN Pembina Pekanbaru - Nur Fitriani; Yufitriana Amir; Nopriadi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Children with disabilities have the same rights in getting education, one of which is sexual education. Sexual education is important for children to avoid unwanted behavior and avoid sexual violence. There are still many parents who consider sexual education taboo and not very important for children. This study aims to identify factors associated with parental behavior in providing sexual education to children with disabilities. This research is a descriptive correlation study. The research sample was 112 respondents who were taken based on inclusion criteria using stratified random sampling technique. The analysis used was bivariate analysis using the Chi-Square test. There were 11 respondents who had poor behavior in providing sexual education to children with disabilities (9.8%), as many as 101 respondents had good behavior in providing sexual education to children with disabilities (90.2%). Statistical test results show there is a significant relationship between education factors (p-value < 0.001), experience factors (p-value = 0.027), knowledge factors (p-value < 0.001), information access factors (p-value = 0.001), perceived control factors (p-value < 0. 001), subjective norm factor (p-value < 0.001), and attitude factor (p-value < 0.001). and there was no significant relationship between occupational factors (p-value = 0.298) and exposure to sexual violence cases (p-value = 0.562). Education, knowledge, experience, access to information, perceived control, subjective norms, and attitudes influence parents' behavior in providing sexual education to children with disabilities.